The Button man : a Hugo Marston novel - Pryor, Mark, 1967- (Pryor, Mark, 1967- Hugo Marston novel, 2014)
"Hugo Marston has just joined the State Department as head of security at the US Embassy in London. His task is to protect a pair of spoiled movie stars, Dayton Harper and his wife Ginny Ferro, whose reckless driving killed a prominent landowner in rural England"--